2011
DOI: 10.1371/journal.pone.0028715
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Management on the Genetic Variation of Wild Pepper, Capsicum annuum var. glabriusculum

Abstract: Management of wild peppers in Mexico has occurred for a long time without clear phenotypic signs of domestication. However, pre-domestication management could have implications for the population's genetic richness. To test this hypothesis we analysed 27 wild (W), let standing (LS) and cultivated (C) populations, plus 7 samples from local markets (LM), with nine polymorphic microsatellite markers. Two hundred and fifty two alleles were identified, averaging 28 per locus. Allele number was higher in W, and 15 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(99 citation statements)
references
References 56 publications
(67 reference statements)
4
92
0
1
Order By: Relevance
“…Although our population was highly structured, we did observe some admixture that can be explained by the large amount of farmers’ seed sharing followed by crossing (González‐Jara et al., ). The pattern shown in Chile de Agua reflects a combination of these two forces: The overall landrace population is structured into different subpopulations genetically, but several of those subpopulations are spread among multiple sites rather than being endemic to one location.…”
Section: Discussionmentioning
confidence: 73%
“…Although our population was highly structured, we did observe some admixture that can be explained by the large amount of farmers’ seed sharing followed by crossing (González‐Jara et al., ). The pattern shown in Chile de Agua reflects a combination of these two forces: The overall landrace population is structured into different subpopulations genetically, but several of those subpopulations are spread among multiple sites rather than being endemic to one location.…”
Section: Discussionmentioning
confidence: 73%
“…In wild chilis (C. annuum var. glabriusculum), González-Jara et al (2011) found greater variation, with 27 alleles per locus. In contrast, with commercial varieties the number of alleles is very low (Kwon et al, 2005), because of their narrow genetic base.…”
Section: Population Genetic Diversitymentioning
confidence: 88%
“…In general, analyses of genetic diversity of the native chili populations of Mexico have revealed a very high degree of variability (Oyama et al, 2006;González-Jara et al, 2011;Pacheco-Olvera et al, 2012). All of this genetic diversity found in the native and wild chili populations of Mexico must be protected and conserved for future studies and for the identification of alleles of agronomic interest.…”
Section: Group/ind Locusmentioning
confidence: 99%
“…Previously, Capsicum germplasm collections have been examined for genetic diversity using accessions from Mesoamerica (Central Mexico to northwestern Costa Rica) to survey geographic origin and understand the domestication process [6, 38]. Recently, STRUCTURE analysis was performed in a Capsicum germplasm collection with 1,352 accessions, which was grouped into six distinct clusters based on genetic analysis with six SSR markers [14].…”
Section: Discussionmentioning
confidence: 99%